Water Infrastructures Facing Sustainable Development Challenges: Integrated Evaluation of Impacts of Dams on Regional Development in Morocco - Paola Minoia; Anna Brusarosco (Fondazione Eni Enrico Mattei (FEEM), 2006)
During the past century, large hydraulic infrastructures have been considered as the most effective tools for increasing water supply and rationalise water management. According to this approach, large infrastructures are seen as catalysts for territorial development and economic progress. More recently, international surveys of results of water supply policies and performances of large dams, show that these structures need to be integrated in more comprehensive Integrated Water Resource Management strategies at catchments scale, to promote equitable and sustainable regional development. The aim of this communication is to present the role of large hydraulic infrastructures within the regional development dynamics with particular attention to the Sebou basin in Morocco, in order to assess some relevant impacts on local communities and their ecosystems. The Sebou region is one of the most important basins in Morocco, in the context of the national strategies and policies of management of water resources, established by the Water Law of 1995. The development of hydraulic infrastructures in the Sebou Basin begun in 1935, with construction of a complex of ten large dams and nine small dams, to provide water for agriculture, domestic and industrial use, and to generate hydropower and control floods, in line with the national water policies that, from the 1960s onwards, looked at large dams as core infrastructures for regional development. A critical view will be given about the coherence of this strategy with the sustainability principles.
Keywords: Q25; Q28; H76; 330; Water Policy; Morocco; Dams; Sustainable Development; Impacts; Talsperre; Regionale Entwicklung; Wasserpolitik; Nachhaltige Entwicklung; Marokko